Predictors of stress among nucleic acid sampling support nurses (NASSNs) during the COVID-19 pandemic - Ping Feng; Liyan Gu; Xiaoying Lu; Min Hu; Yanqiu Weng; Wenyao Chen (Human Resources for Health)
Abstract Background The COVID-19 pandemic has forced nucleic acid detection to be essential for prevention and control. The psychological and physical health of healthcare staff who conducted nucleic acid sampling (NAS) should be paid attention to. This study aims to investigate the status and explore the predictors of stress among nucleic acid sampling support nurses (NASSNs) by an online survey. Material and methods Totally 388 NASSNs were recruited through cluster random sampling for the research. An online cross-sectional survey with structured questionnaires was used, including socio-demographic information, the stressor scale of nucleic acid sampling nurses (SSNASN), and the challenge–hindrance stress scale (CHSS). T-tests, ANOVA, and multivariable linear regression model were used to analyze data. Results A total of 324 NASSNs filled out questionnaires online with a response rate of 83.51%. NASSNs had an overall mean score of (2.199 ± 0.917) for challenge stress and (2.014 ± 0.805) for hindrance stress. The item "the amount of responsibility I have" scored highest in the challenge stress dimension, while "the lack of job security I have" scored highest in the hindrance stress dimension. The predictors of challenge and hindrance stress include concern about the preparedness of NASSNs and their families, working environment, and competence of emergency disposal. An additional socio-demographic predictor of challenge stress was motivation, while that of hindrance stress was longer nursing experiences. Conclusions During the COVID-19 pandemic, stress among NASSNs was moderately low. The factors detected to be predictors of stress include motivation, nursing experiences, concern about the preparedness of NASSNs and their families, working environment, and competence in emergency disposal. Therefore, in advance of responding to a public health event, we recommend that subsequent short-term psychological counseling be given to healthcare workers and accompanying psychological counseling be provided to prevent the emergence of mental health problems thereafter.